OPTIMALISASI KANDUNGAN ZAT GIZI (Protein, Lemak, Karbohidrat dan Serat) DAN DAYA TERIMA COOKIES DENGAN PENAMBAHAN TEPUNG KULIT PISANG RAJA - Annafi Tazhkira; Dwi Novri Supriatiningrum; Sutrisno Adi Prayitno (Universitas Muhammadiyah Gresik, 2021)
Plantain peels have a high crude fiber content and can be processed into cookies. The benefits o banana peels as a substitusi for making cookies to increase fiber levels. The research objective was to determine the effect of adding plantain peel flour on nutrients and sensory cookies. The research method used a completely randomized experimental design with 5 formulations with codes F0, F1, F2, F3, and F4. The defference in sensory test is known by the friedman test and the nutrient test is known by the One Way Analysis of Variance (ANOVA) test and then the difference test is carried out with the LSD test with a level of 5%. The results of the sensory test analysis showed that there was an effect of substitution of plantain peel flour on the sensory cookies of banana peel flour which included color, aroma, teste and texture, indicating that H0 was rejected and H1 was accepted, which was a significant difference. The best or highest analysis results are at 0% substitution and the lowest is 30%. Meanwhile, the analysis off the nutritional test showed that the highest protein contest was in the substitution cookies for plantain peel flour (0%) 0f 8.32, the highest fat (0%) was 17.90, the highest carbohydrate (40%) was 70.10, the highest fiber (40%) of 3.35. conclusion the best cookies are in formula F2 (20%) with consumption o 12 pieces of plantain skin flour cookies/day can prevent or reduce the risk of KEK (Chronic Energy Deiciency) in adolescent.